PENGARUH BRAND IMAGE DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI KASUS PRODUK LOGITECH) - Fakhri Ade Putra; Ahmad Mardalis (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The purpose of this study was to analyze the effect of brand image and social media marketing on consumer purchasing decisions. This research method is quantitative. The population in this study are all consumers who have shopped for Logitech products at ELS ID. Sampling in this study used non probability sampling with purposive sampling technique. The number of samples in this study were 221 respondents. The data source for this research is primary data. The data collection technique used a questionnaire. Research data analysis techniques with the help of SPSS software. The result of this study is that Brand Image has a significant effect on Consumer Purchasing Decisions. Social Media Marketing has a positive effect on Consumer Purchasing Decisions. Simultaneously Brand Image and Social Media Marketing have an effect on Consumer Purchasing Decisions